School Subject Community in Times of Death of the Subject - Lopes, Alice Casimiro; Costa, Hugo Heleno Camilo (Policy futures in education, 2019)
In this article, we aim to theorize about the understanding of a school subject community in a discursive framework, particularly concerned with the theoretical and strategic possibilities of this notion in the research of curriculum policy. In these times, in which the death of the centered, conscious and cohesive Subject is assumed, what precisely do we mean by subjectivity (collective or not) when we are talking about a school subject community? Goodson’s theory, in relation to structural concerns, organized socio-historical conditions to explain these phenomena. Therefore, we consider it relevant to reconceptualize Goodson´s school subject community category, or even enact its deconstruction, to the extent that we propose to include other subjectivity senses through post-structural theory. We point out that our distance from Goodson´s reading of ‘community’ takes place, also, due our distance from the assumption of the existence of common, positive data, capable of generating cohesion and/or unity among individuals. Hence, with our perspective directed towards subjectivity in the context of post-structural and political-curricular thinking, based on Laclau’s theory of discourse, we discuss the possibility of thinking about the subjectivity of a community, in this case the school subject community, or its subjectivations. In conclusion, the school subject community is the result – albeit precarious, temporary and contingent – of discursive articulation. The school subject community, through the argument we have built, is the set of subjectivities formed in provisional operations in the discursive field named school subject.